Safety First: Assessing and Comparing Laboratories in Junior High Schools in Samarinda City - Erna Sari; Grecellia Mei Magdalena Dakhi; Fitri Azkia; Siti Bulkiah; Ramadhan Purbaya; Nurul Fitriyah Sulaeman (ScienceEdu, 2024)
The importance of laboratory management in science education at schools is crucial for creating an optimal learning environment. This qualitative research was conducted at Junior High School A and Junior High School B in Samarinda, focusing on laboratory safety and management. The results indicate a strong awareness of potential hazards, equipment safety, and user safety. However, differences in material safety management were identified, providing valuable insights for improvement. Research recommendations emphasize the need for educational efforts on safety and occupational health in school laboratories to enhance safety standards.